(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the linguistic features of phraseological units, their classification, difficulties that arise when translating phraseological units, and methods of translating them from English into Russian.